IDENTIFICATION OF NATIONAL IDENTITY THROUGH SPORTS AND CULTURAL ACTIVITIES - Ben Khaled Hadj,; Touati Hayat,; Mokrani Djamel,; Guezgouz Mohamed, (Sport Scientific And Practical Aspects, 2025)
Introduction: The study aims to determine the role of sports and cultural activities in the establishment of national identity among primary school students. Methods: It has thus applied to a random sample of 300 pupils of the fifth year of primary school in the city of Mostaganem, by means of a descriptive approach based on the technique of the survey, which is the most suitable for the object of this study. For this purpose, we have opted for the following statistical tool: Percentages k2 for the computation of the scale (form) presented to the students who are mainly characterized by honesty and objectivity. Results:After collecting and processing the results, we have been able to reach the conclusion that sports activities contribute to an above-average degree to the consolidation of national identity among primary school students. As for the so-called complementary activities (cultural activities), they contribute significantly to the reinforcement of national identity to a very large extent, exceeding 75%. Discussion: Thus, in order to strengthen national identity among young people in general and primary school students in particular, the following recommendations: the need to consider the individual preferences of the students – Satisfy their needs and make sure not to stifle their creativity strengthening their sense of motivation by involving them in all activities. Limitations: Despite the high number of the participants, the findings of the study are limited to the analyses of quantitative data as the main source. Conclusions: The school mission goes far beyond educating students; it goes as far as teaching them to love their country, to be devoted and faithful to the history and the nation's ancestral glories.